The Development of Self-Control Scale in Social Media - Indah Dwi Febrianti; Mariza Ningtyas Febriyanti; Isna Rahma Adhania; Utari Nur Khasanah; Enno Arjuni Putri Andiny; Aftina Nurul Husna (Prosiding University Research Colloquium, 2021)
The purpose of this study was to develop a psychological scale of self-control insocial media. Self-control is the ability to control behavior and resist temptationsthat arise from within so as to be able to take action to avoid unwantedconsequences, self-control has three aspects, namely the ability to control behavior,cognitive control and decision control. The stages of this research includeconfirming the measuring area by selecting the attribute of self-control, thenmaking a blueprint for the self-control scale to limit the concept of self-control.Item writing refers to self-control indicators in social media, the content validitytest involves 3 raters and the readability test involves 4 respondents according tothe criteria. The data collection technique uses Convenien sampling, namely byuploading the "Social Media" questionnaire link on social media accounts. Thereliability test on the self-control scale produces a Cronbach Alpha coefficient of0.903, meaning that the reliability of the scale is very good. The final result of thisscale consists of 20 items.